Cyclic oxidation behavior of selected commercial NiCr-alloys for engine exhaust valves in wet air environment between 800 and 950 °C. (February 2023) - Romedenne, M.; Haynes, A.; Pillai, R.
Abstract: The impact of water vapor on the cyclic oxidation behavior of four commercial Ni-based superalloys (N80A, N90, R41 and H282) was investigated between 800 and 950 °C. Oxidation- and volatilization-induced Cr loss accelerated the transition from protective and adherent oxide formation (Cr 2 O 3 ) to mixed oxides that significantly spalled at 950 °C for H282 and R41. The accelerated oxidation, Cr depletion, and spallation susceptibility for R41 and to a lesser extent for H282 compared to N80A and N90 was related to the higher fraction of γ ', which led to increased Ti incorporation into the Cr 2 O 3 scale in the presence of water vapor. Highlights: The cyclic oxidation of Cr2 O3 former superalloys was studied in air and air ＋ 10%H2 O. The alloys degraded by oxidation and spallation especially in water vapor. γ ' stability determined the extent of Ti release and inclusion in the oxide. Water vapor and Ti incorporation result in the breakdown of the Cr2 O3 scale.